2020
DOI: 10.14338/ijpt-19-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Secondary Malignancies following Proton versus Photon Radiation for Oropharyngeal Cancers

Abstract: Purpose There has been a recent epidemic of human papillomavirus (HPV)–positive oropharyngeal cancer, accounting for 70% to 80% of diagnosed cases. These patients have an overall favorable prognosis and are typically treated with a combination of surgery, chemotherapy, and radiation. Because these patients live longer, they are at risk of secondary malignant neoplasms (SMNs) associated with radiation therapy. Therefore, we assessed the predicted risk of SMNs after adjuvant radiation therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The recent study by Jain et al focused on the predicted risk of SPM in a cohort of patients with HPV-positive OPC subjected to transoral robotic surgery (TORS) and selective neck dissection followed by adjuvant IMPT [ 36 ]. Both IMPT and IMRT plans were generated for each patient, and previously reported models of organ-specific radiation-induced cancer incidence were used to address the aim of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The recent study by Jain et al focused on the predicted risk of SPM in a cohort of patients with HPV-positive OPC subjected to transoral robotic surgery (TORS) and selective neck dissection followed by adjuvant IMPT [ 36 ]. Both IMPT and IMRT plans were generated for each patient, and previously reported models of organ-specific radiation-induced cancer incidence were used to address the aim of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Jain et al [ 40 ] reported on 13 patients with HPV-positive OPSCC treated with TORS and postoperative IMPT, treating bilateral fields to 60 Gy in 30 fractions at the University of Pennsylvania. When compared with IMRT, IMPT resulted in significant reductions in the mean doses to the mandible, contralateral parotid, lung, and skin organ equivalent doses ( P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, young age, favorable prognosis, and previous irradiation in the head and neck region were other important factors that led to the clinicians’ preference for PT [ 18 ]. It is generally accepted that PT is a preferred treatment option for pediatric HNC patients, due to the advantage of low dose spread in tissue, with a potential reduction in secondary malignancies [ 66 ].…”
Section: The Challenge Of Patient Selectionmentioning
confidence: 99%